Mental health consequences of military sexual trauma: results from a national survey in the French military - Caroline Moreau; Sandrine Duron; Dina Bedretdinova; Aline Bohet; Henri Panjo; Nathalie Bajos; Jean Baptiste Meynard (BMC, 2022)
Abstract Background Military sexual trauma (MST) is a major public health concern, given its prevalence and mental health sequelae. This phenomenon is particularly prevalent among women in the US military, although more cases involve men given their overrepresentation. Little is known about MST and its consequences in other military settings, including in Europe. Methods This study draws from a national survey in the French military, including 1268 servicemen and 232 servicewomen. We conducted bivariate and multivariate analysis, using simple and multinomial logistic regressions to evaluate the associations between different forms of MST (repeated sexual comments alone/one form of sexual oppression (coercion, repeated verbal unwanted attention or assault)/ several sexual stressors) and symptoms of depression and of positive post-traumatic stress disorder (PTSD) screening scores. Results Women were both more likely to experience MST and to experience more severe forms of MST than men. Women were also more likely than men to report mental health symptoms (31% versus 18% for symptoms of depression and 4.0% versus 1.8% for positive PTSD screening scores). Different forms of MST were associated with different levels of psychological distress. Women reporting repeated sexual comments alone had higher odds of depressive symptoms (OR=3.1 [1.7, 5.5]) relative to women with no MST. Likewise, the odds of depressive symptoms were 6.5 times higher among women and 8.0 times higher among men who experienced several sexual stressors relative to those who reported no MST. We also found higher relative risk of subthreshold PTSD screening scores among women reporting any form of sexual stressor, including sexual comments alone (RRR = 4.5 [2.8, 7.4]) and an elevenfold increase in the relative risk of positive PTSD screen scores (RRR = 11.3 [2.3, 55.6]) among women who experienced several sexual stressors relative to women with no MST. Conclusion MST is associated with mental health distress among service members in the French military, especially for women. The heightened risk of MST coupled with psychological sequelae call for preventive programs to reduce MST and for screening programs to provide adequate psychological support.